Carbon Emissions and Urbanization in ASEAN-5 Countries - Winny Perwithosuci; Hamim Zaky Hadibasyir; Muhammad Arif (Optimum: Jurnal Ekonomi dan Pembangunan, 2022)
The population in the world reach 7.5 billion in 2019. Population living in urban area is one of the drivers of cabon emissions. This study aims to estimate the relationship between urbanization, GDP, trade openness, and coal consumption on carbon dioxide emissions in ASEAN-5 countries which are Indonesia, Malaysia, Thailand, Philippines, and Vietnam from 1990 to 2020. The data generated from British Petroleum and World Bank. This current study employs Fixed-Effect estimation model to estimate the data. The result revealed there is positive relationship between urban population as proxy of urbanization, GDP, trade openness, and coal consumption. Policies should highlight the utilization of low-carbon techlonogies and renewable energy to reduce carbon emissions.